Bibliometric Computational Mapping Analysis of Graphene-Based Surfaced – Enhanced Raman Scattering (SERS) During 2012 – 2022 - Afviva Nissa Vahendra; Asep Bayu Dani Nandiayanto (Advance Sustainable Science Engineering and Technology, 2022)
This study aims to examine the development of research related to Graphene-Based Surfaced-Enhanced Raman Scattering (SERS) through a bibliometric approach to computational mapping analysis using VOSviewer. The acquisition of article data was obtained from the Google Scholar database using the publish or perish reference manager application. The keywords used to guide the process of searching for the title and abstract of the article were "Graphene, SER, surface enhanced raman scattering, nanoparticle". A total of 920 articles were obtained which were considered related to the topic of this research. The study period used as study material is Google Scholar indexed articles for the last 10 years (2012 to 2022). The results showed that the Graphene-Based Surfaced-Enhanced Raman Scattering (SERS) research can be separated into 4 terms:Raman Spectroscopy, Graphene, Nanoparticle and Surface. The term “Raman Spectroscopy” is associated with 189 links with total link strength 1539 The term “Graphene” has 198 links with total link strength 2036 the term “Nanoparticle” has 199 links with total link strength in 2739 and the term “Surface” has 189 links with total link strength 1651. The results of the analysis of the development of Graphene-Based Surfaced-Enhanced Raman Scattering (SERS) in the last 10 years show an increase. However, in 2020-2021, there was a slight decrease from 136 in 2020 to 135 in 2021. The increase in research occurred from 2014 - 2020 (49, 63, 80, 99, 105,116 and 136 publications per year respectively). While the popular Graphene-Based Surfaced-Enhanced Raman Scattering (SERS) research was carried out in 2020, there were 136 studies. From the results of research on article data using VOS viewer on Graphene-Based Surfaced-Enhanced Raman Scattering (SERS) and its relationship to the problem area, the results show that there has been an increase over the last 10 years. This study can be an initial consideration for future researchers who will conduct research related to this research topic.